Methylglyoxal Augments Angiotensin II-Induced Contraction in Rat Isolated Carotid Artery - Masashi Mukohda; Hideyuki Yamawaki; Muneyoshi Okada; Yukio Hara (Elsevier, 2010)
Abstract.: Methylglyoxal (MGO), a metabolite of glucose, accumulates in vascular tissues of a hypertensive animal. In the present study, we examined the effect of MGO on angiotensin (Ang) II-induced contraction of rat carotid artery. Treatment of carotid artery with MGO (420 μM, 30 min) significantly augmented Ang II (0.1 to 30 nM)-induced concentration-dependent contraction. The effect was abolished by the removal of endothelium. BQ-123 (1, 5 μM), an endothelin A- receptor blocker, had no effect on the MGO-induced enhancement of Ang II-induced contraction. AL8810 (1 μM), a prostaglandin F2α-receptor blocker, or SQ29548 (1 μM), a thromboxane A2- receptor blocker, was also ineffective. However, tempol (10 μM), a superoxide scavenger, and catalase (5000 U/mL), which metabolizes hydrogen peroxide to water, significantly prevented the effect of MGO. Combined MGO and Ang II treatment increased reactive oxygen species (ROS) production. Apocynin (10 μM) or gp91ds-tat (3 μM), an inhibitor of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, significantly prevented the effect of MGO. Gp91ds-tat or an Ang II type 1-receptor (AT1R) blocker, losartan (10 μM), prevented the MGO-mediated increased ROS production. The present study revealed that MGO augments Ang II-induced contraction by increasing AT1R-mediated NADPH oxidase-derived superoxide and hydrogen peroxide production in endothelium of rat carotid artery. Keywords:: glucose metabolite, vascular endothelium, angiotensin, reactive oxygen species, smooth muscle contractility